Prognostic value of intra-left ventricular electromechanical asynchrony in patients with mild hypertrophic cardiomyopathy compared with power athletes. Issue 3 (27th February 2006) - D'Andrea, A; Caso, P; Cuomo, S; Salerno, G; Scarafile, R; Mita, C; De Corato, G; Sarubbi, B; Scherillo, M; Calabrò, R
Abstract : Objectives: We sought to assess the indexes of myocardial activation delay, using Doppler myocardial imaging (DMI), as potential diagnostic tools and predictors of cardiac events in patients with hypertrophic cardiomyopathy (HCM) compared with power athletes. Background: the distribution and magnitude of left ventricular (LV) hypertrophy are not uniform in patients with HCM, which results in heterogeneity of regional LV systolic function. Methods: The study population comprised 70 young patients with HCM (mean (SD) age 29.4 (5.9) years) with mild septal hypertrophy (15–19 mm) and 85 age and sex matched athletes with septal thickness >12 mm, followed up for 44.4 (10.8) months. Using pulsed DMI, myocardial peak velocities, systolic time intervals, and myocardial intraventricular and interventricular systolic delays were measured in six different basal myocardial segments. Results: DMI analysis showed in HCM lower myocardial both systolic and early diastolic peak velocities of all the segments. Patients with HCM also showed significant interventricular and intraventricular delay (p<0.0001), whereas athletes showed homogeneous systolic activation of the ventricular walls. During the follow up, seven sudden deaths occurred in the HCM group, while no cardiovascular event was observed in the group of athletes. In patients with HCM, intraventricular delay on DMI was the most powerful independent predictor of sudden cardiac death (p<0.0001). An intraventricular delay >45 ms identified with high sensitivity and specificity patients with HCM at higher risk of ventricular tachycardia and cardiac events (test accuracy 90.6%). Conclusions: DMI may be a valid supporting tool for the differential diagnosis between HCM and "athlete's heart". In patients with HCM, DMI indexes of intraventricular delay may provide additional information for selecting subgroups of patients with HCM at increased risk of ventricular arrhythmias and sudden cardiac death at follow up. Accordingly, such patients may benefit from early intensive treatment and survey. Miniabstract: Doppler myocardial imaging may represent a valid supporting tool for the differential diagnosis between mild hypertrophic cardiomyopathy (HCM) and "athlete's heart". In patients with HCM, DMI indexes of intraventricular delay may provide additional information for selecting subgroups of patients with HCM at increased risk of ventricular arrhythmias and sudden cardiac death at follow up.